New ICDs Safe, Effective After MRI in Evera MRI and ProMRI Studies - Nichols, Emma Hitt (MD Conference Express, 2015)
Two new implantable cardioverter defibrillator systems developed for compatibility with magnetic resonance imaging demonstrate safety and efficacy in the Evera MRI and ProMRI trials, with no significant changes in ventricular pacing threshold < 5.0 V or ventricular sensing. In addition, there were no serious device-related events in both studies.